Islamic Civilization and the Digital Economy: Building a Sharia Economy in Modern Era - Mardiyyah, Ema; Harahap, Nikma Sari; Febriza, Milla (Musyarakah: Journal of Sharia Economic (MJSE), 2025)
Islamic civilization has made great contributions in various fields, including economics, with principles that emphasize justice, balance and sustainability. principles that emphasize justice, balance, and sustainability. Along with digital transformation brings new challenges and opportunities for Islamic economics, which can integrate Islamic values with for Islamic economics, which can integrate Islamic values with modern technology. modern technology. This research aims to examine how Islamic civilization can build Islamic economics in the digital era through the utilization of technology such as fintech, blockchain, and e-commerce. technology such as fintech, blockchain, and e-commerce. This research uses a literature review approach. Digital economy can expand sharia financial inclusion, facilitate access to sharia-based financial services, and create innovations that meet the needs of sharia financial services, and create innovations that suit the needs of modern society. needs of modern society. Nonetheless, the main challenge faced is ensuring that digital economic practices remain in line with sharia principles, such as the prohibition of riba, gharar and maysar. principles, such as the prohibition of riba, gharar, and maysir. In this context, this research explores how digital technology can be applied in the Islamic economy without violating Islamic principles, as well as how regulation and supervision can ensure its integrity. Research results show that despite the challenges, the integration of the digital economy with Shariah principles can create a more inclusive, equitable and sustainable economic system, which can contribute to the development of a fairer global economy. This research contributes to the literature on Islamic economic development in the digital age and offers insights into ways to ethically utilize technology in accordance with Islamic values